A participação política de imigrantes germânicos no Rio Grande do Sul: os Brummer Kahlden, Haensel, Koseritz e ter Brüggen, 1851-1881 - Piassini, Carlos Eduardo (2016)
This study, integrated to researches in developing at the research area "Border, Politics and Society" of the Master's Graduate Program in History at the Universidade Federal de Santa Maria (PPGH-UFSM), Rio Grande do Sul, Brazil, counting with assistance of CAPES/DS, aimed to investigate the forms of political participation of the German immigrants Karl von Koseritz, Frederico Haensel, Karl von Kahlden and Whilhelm ter Brüggen during the second half of the nineteenth century, in Rio Grande do Sul, during which one was still very restricted the participation of immigrants in the official political life on account the limitations imposed by the electoral legislation from century XIX and restrictions linked to income. These characters were selected because of two common elements between them: were the first group of foreign of Germanic origin that reach the office of Provincial Deputy in Rio Grande do Sul in the 1880's, and composed the mercenary troops of Brummer contracted in 1851 to act with the Brazilian Imperial Force in the War against Oribe and Rosas (1851-1852). The time frame was defined taking into account the year of 1851 as a landmark of the arrival in Brazil of the investigated characters, and the year of 1881 as the enactment of the Saraiva Law, which expanded the political participation of foreigns in elective office. The study was realized by investigation of participation of these four individuals in different social spaces in which they circulated. The political and life trajectories of they showed similarities. Thus, they formed a group with great specificity who served in public office, in Freemasonry, in recreational and charities associations, in trade and in press. The main attention was paid to public office who they exercised. Karl von Kahlden as Director Colonial, Frederico Haensel as Vice Consul of Prussia, Karl von Koseritz as Interpreter Colonization Agent and Wilhelm ter Brüggen as Consul of Prussia.